Common Core curriculum maps in English language arts, grades 9-12 - Common Core, Inc. (San Francisco, CA : Jossey-Bass, 2012)
'The first books to present specific guidance for teaching the Common Core State Standards. Forty-three states plus the District of Columbia and the U.S. Virgin Islands have signed on to adopt the Common Core State Standards (CCSS). The need for curriculum guides to assist teachers in helping students meet these standards has become imperative. Created by teachers, for teachers, the research-based curriculum maps in this book present a comprehensive, coherent sequence of thematic units for teaching the skills outlined in the CCSS for English language arts in Grades 9-12. Teachers can use the maps to plan their year and craft their own more detailed lesson plans. Each grade is broken down into six units that include focus standards, suggested works, sample activities and assessments, lesson plans, and more The maps address every standard in the CCSS, yet are flexible and adaptable to accommodate diverse teaching styles Any teacher, school, or district that chooses to follow the Common Core maps can be confident that they are adhering to the standards'--
Includes index.
Keywords: Language arts (Secondary) -- Curricula -- United States -- States; Language arts (Secondary) -- Standards -- United States -- States